2013
DOI: 10.1158/0008-5472.can-12-3947
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic NRAS, Required for Pathogenesis of Embryonic Rhabdomyosarcoma, Relies upon the HMGA2–IGF2BP2 Pathway

Abstract: Embryonic rhabdomyosarcoma (ERMS) is the most common soft-tissue tumor in children. Here, we report the identification of the minor groove DNA-binding factor high mobility group AT-hook 2 (HMGA2) as a driver of ERMS development. HMGA2 was highly expressed in normal myoblasts and ERMS cells, where its expression was essential to maintain cell proliferation, survival in vitro, and tumor outgrowth in vivo. Mechanistic investigations revealed that upregulation of the insulin–like growth factor (IGF) mRNA-binding p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…It will be of interest to see whether there is any crosstalk between these LncRNAs or whether the newly discovered IMP2 binding is a mechanism particular to the MyoD-LncMyoD-IMP pathway (Figure 7B). Since IMPs are involved in regulating cell proliferation and organ development in many tissues ( Li et al, 2012Li et al, , 2013, it will be of great interest to identify and study IMP-binding LncRNAs in other systems. Disturbed myogenesis may be a component of the mechanism of diseases such as cachexia, sarcopenia, and especially muscular dystrophy (where a pattern of muscle breakdown and regeneration repeats itself until the muscle's regenerative capacity is depleted).…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to see whether there is any crosstalk between these LncRNAs or whether the newly discovered IMP2 binding is a mechanism particular to the MyoD-LncMyoD-IMP pathway (Figure 7B). Since IMPs are involved in regulating cell proliferation and organ development in many tissues ( Li et al, 2012Li et al, , 2013, it will be of great interest to identify and study IMP-binding LncRNAs in other systems. Disturbed myogenesis may be a component of the mechanism of diseases such as cachexia, sarcopenia, and especially muscular dystrophy (where a pattern of muscle breakdown and regeneration repeats itself until the muscle's regenerative capacity is depleted).…”
Section: Discussionmentioning
confidence: 99%
“…By bioinformatics prediction software for potential target validation, it has been shown a few genes related to let‐7b. We focus on the IGF2BP2 because some recent reports have shown that HMGA2 has a relationship with IGF2BP2 and the axis of HMGA2‐IGF2BP2 complex has the functions as a critical regulator of satellite cell activation during skeletal muscle development . Let‐7b preferentially regulates or modulates transcription factor HMGA2, which is required to transcribe IMP2 .…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP2 is known to be associated with T2D [25,26], and has been shown to modulate cell survival and be associated with cancer metastasis and the expression of oncogenic factors (KRAS, MYC and MDR1) [27]. Li et al found that the HMGA2-IGFBP2-NRAS signaling pathway was a critical oncogenic driver in embryonic rhabdomyosarcoma [28]. IGF2BP2 rs4402960 has also been reported to modify colorectal cancer risk independently and to be positively associated with prostate cancer [29,30].…”
Section: Discussionmentioning
confidence: 99%